Gut microbes shape microglia and cognitive function during malnutrition. Issue 5 (12th January 2022) - Bauer, Kylynda C.; York, Elisa M.; Cirstea, Mihai S.; Radisavljevic, Nina; Petersen, Charisse; Huus, Kelsey E.; Brown, Eric M.; Bozorgmehr, Tahereh; Berdún, Rebeca; Bernier, Louis‐Philippe; Lee, Amy H. Y.; Woodward, Sarah E.; et al.
Abstract: Fecal‐oral contamination promotes malnutrition pathology. Lasting consequences of early life malnutrition include cognitive impairment, but the underlying pathology and influence of gut microbes remain largely unknown. Here, we utilize an established murine model combining malnutrition and iterative exposure to fecal commensals (MAL‐BG). The MAL‐BG model was analyzed in comparison to malnourished (MAL mice) and healthy (CON mice) controls. Malnourished mice display poor spatial memory and learning plasticity, as well as altered microglia, non‐neuronal CNS cells that regulate neuroimmune responses and brain plasticity. Chronic fecal‐oral exposures shaped microglial morphology and transcriptional profile, promoting phagocytic features in MAL‐BG mice. Unexpectedly, these changes occurred independently from significant cytokine‐induced inflammation or blood–brain barrier (BBB) disruption, key gut‐brain pathways. Metabolomic profiling of the MAL‐BG cortex revealed altered polyunsaturated fatty acid (PUFA) profiles and systemic lipoxidative stress. In contrast, supplementation with an ω3 PUFA/antioxidant‐associated diet (PAO) mitigated cognitive deficits within the MAL‐BG model. These findings provide valued insight into the malnourished gut microbiota‐brain axis, highlighting PUFA metabolism as a potential therapeutic target. Main Points: Early‐life malnutrition and specific gut microbes shape cognition and microglia in mice. Altered microglial features occur independently from significant neuroinflammation or BBB deficits, but were linked to impaired lipid metabolism. PAO diet (ω3 PUFA/antioxidant‐associated supplement) improves cognitive features of malnutrition.